2023
DOI: 10.1021/acs.jpcc.3c00262
|View full text |Cite
|
Sign up to set email alerts
|

The Dramatic Effect of Water Structure on Hydration Forces and the Electrical Double Layer

Abstract: Forces between hydrophilic surfaces mediated by water are important in various systems from lipid membranes and solid surfaces to colloids and macromolecules, first discovered as a significant addition to DLVO forces at the nanoscale. These “hydration forces” have been studied in great detail experimentally using osmotic stress measurements, surface force apparatus, and AFM, and they have also been the subject of multiple theories and simulations. One spectacular feature observed in experimental and simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…It has also recently been shown that the smearing of the surface (and of the boundary condition) may dramatically affect the polarization profiles; a strong and nontrivial effect is also expected to come from the lateral inhomogeneity of the surfaces . In the present study we have considered ideally smooth, laterally homogeneous, and sharp surfaces, whereas in reality in many systems they are not as such.…”
mentioning
confidence: 98%
“…It has also recently been shown that the smearing of the surface (and of the boundary condition) may dramatically affect the polarization profiles; a strong and nontrivial effect is also expected to come from the lateral inhomogeneity of the surfaces . In the present study we have considered ideally smooth, laterally homogeneous, and sharp surfaces, whereas in reality in many systems they are not as such.…”
mentioning
confidence: 98%
“…Third, density variations have a direct effect on the adsorption of ions due to steric exclusion . In particular, FF MD simulations show that ions at charged hydrophobic surfaces accumulate between the peaks in the oscillating water density profile, an effect expected to vanish for surfaces exhibiting a roughness of as little as the size of a molecule . In these simulated density profiles, the traditional interfacial layers can be clearly identified, viz., partially dehydrated ions between the surface and the first density peak form the inner Helmholtz layer of adsorbed ions, fully hydrated ions between the first two density peaks form the outer Helmholtz layer, and the rest of the fluid forms the diffuse layer.…”
Section: Molecular Structure Of the Pristine Water Interfacementioning
confidence: 92%
“…Water-mediated hydration forces are caused not only by molecular density fluctuations. The coupling between polarization and molecular density fluctuations gives rise to a resonance peak in the wave-vector-dependent nonlocal dielectric response function, which in turn causes an oscillatory decay in the water-mediated forces between smooth surfaces . Yet to show that the oscillatory structure is present also in the absence of the AFM tip, the interfacial density of water oxygen can be extracted from a fit to X-ray spectroscopy data.…”
Section: Molecular Structure Of the Pristine Water Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated mean-field models of the EDL were developed to address some of these effects. 15–21…”
Section: Introductionmentioning
confidence: 99%